ChemInform Abstract: Iron‐Catalyzed Hydroboration: Unlocking Reactivity Through Ligand Modulation. Issue 52 (6th December 2016) - Espinal‐Viguri, Maialen; Woof, Callum R.; Webster, Ruth L.
Abstract: A new catalytic system without the requirement of external reducing agents or activators is developed which is applied to the hydroboration of a broad range of alkenes, including terminal alkyl and styrene derivatives, internal alkenes and dialkenes.